Using rapid quantification of adenosine triphosphate (ATP) as an indicator for early detection and treatment of cyanobacterial blooms. (1st May 2019) - Greenstein, Katherine E.; Wert, Eric C.
Abstract: Early detection of harmful cyanobacterial blooms allows identification of potential risk and appropriate selection of treatment techniques to prevent exposure in recreational water bodies and drinking water supplies. Here, luminescence-based adenosine triphosphate (ATP) analysis was applied to monitor and treat cultured and naturally occurring cyanobacteria cells. When evaluating lab-cultured Microcystis aeruginosa, ATP concentrations (≤252, 000 pg/mL) had improved sensitivity and correlated well (R 2  = 0.969) with optical density measurements at 730 nm (OD730; ≤0.297 cm −1 ). Following one year of monitoring of a surface water supply, ATP concentrations (≤2000 pg/mL) correlated (R 2  = 0.791) with chlorophyll- a concentrations (≤50 μg/L). A preliminary early warning threshold of 175 pg ATP/mL corresponded with 5 μg/L chlorophyll- a to initiate increased monitoring (e.g., of cyanotoxins). Following oxidation processes (i.e., chlorine, chloramine, ozone, permanganate), ATP was demonstrated as an indicator of cell lysis and a threshold value of <100 pg/mL was recommended for complete release of intracellular cyanotoxins. ATP was also used to assess efficacy of copper (Cu(II)) treatment on cyanobacteria-laden surface water. While 24-h exposure to 2.5 mg Cu(II)/L did not impact chlorophyll- a, ATP decreased from 13, 500 to 128 pg/mL indicating metabolic activity was minimized. Ultimately, ATP analysis holds promise for early detection and mitigation of potentially harmful algal blooms based on superior sensitivity, independence from cell morphology artifacts, rapid time for analysis (<10 min), and ease of deployment in the field compared to conventional methods. Graphical abstract: Image 1 Highlights: ATP concentrations correlated with cyanobacteria cell counts and chlorophyll- a. ATP correlated with chlorophyll- a in Lake Mead, a drinking water supply. ATP was applied as an indicator of cell lysis during chemical water treatment. Intracellular ATP analysis holds promise for early detection of biological events.